(untitled) (Third Sector Social Economic Review, 2017)
Leadership has been one of the important subjects in management. There has been numerous studies regarding subject and leadership has become more important each day. Studies regarding leadership has changed structure and the most common use of leadership have been transactional and transformational leadership. Since, leadership is the ability of convincing members of a group to achieve certain objectives willingly, effect of leadership on organizational performance has become one of the focussed subjects. In this study, the relationship between transformational leadership and R&D performance has been researched. In order to measure transformational leadership level, Bass and Avolio’s Multifactor Leadership Questionnaire has been used. For R&D performance, Hirst’s R&D performance model which has been developed in 2000 has been used as a survey. Data has been collected from managers or manager candidates that work at R&D departments of defence industy companies located in Ankara, which is the center of Turkish defence industry. SPSS for Windows application has been used to analyze collected data. Using SPSS, mean, frequency and frequency percent distribution, reliability test, correlation and regression analysis have been done. Afterwards, all results have been evaluated.